Cultivation, Identification, and Parameter Optimization of Chicken Embryo Fibroblast (CEF) in Primary Culture - Qureshi, Muhammad Naqeeb Ur Rehman; Qayyum, Mazhar; Riaz, Aayesha; Qureshi, Muhammad Anees Ur Rehman; Rasool, Atta; Kanwal, Maria (Scientific Inquiry and Review, 2024)
Chicken eggs have frequently been used as research models for pathogenic disease processes and human research biology. The inflammatory responses and immune suppressions significantly influence the growth of chicken embryo fibroblasts’s (CEFs) growth. In the current study, CEFs were isolated, grown and effect of temperature, serum, incubation, and viral growth were examined. An inverted microscope confirmed morphological features and spindle shape CEFs. It was revealed that 37 ºC temperature, 24-48 h incubation time, and 10% fetal bovine serum (FBS) solution are best optimal conditions for cultivation of CEFs. Viral growth was more prominent with an increase in incubation time span. Haemagglutination (HA) and haemagglutination inhibition (HI) assays confirmed 1024 virus counts and 6 titer of blood. The current study is a contribution to the literature that could be explored to model a platform for the development of viral vaccines by using CEFs cultures.